(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Monetary policy bodies in almost all countries of the world, regardless of the level of development of the economy and financial market, were not ready for the emergence and rapid development of digital currencies and, in particular, for their virtual variety - cryptocurrency.The development of technology constantly brings something new into our life, sometimes completely incomprehensible and unpredictable. An example of such a phenomenon is cryptocurrency. Many studies aimed at finding the exact factors on which the rate of cryptocurrencies may depend have not shown significant results. This study is aimed at finding the dependence of the cryptocurrency exchange rate on updates in the technical aspect of the cryptocurrency mining process.